Malay Comparative and Superlative - Bakar, Norsofiah Abu; Yusoff, Radiah (European Publisher, 2019)
In the Malay language, comparatives, such as ‘lebih’ (<> more) and ‘kurang’ (<> less), and superperlatives, such as ‘paling’ (<> most’) and ‘sangat’ (<> very), are said to exist with an adjective phrase, for example, ‘lebih besar’ (<> bigger), ‘kurang manis’ (<> less sweet), ‘paling cantik’ (<> most beautiful’), and ‘sangat besar’ (<> biggest). Comparatives and superlatives in Malay are categorised as intensifiers. Comparatives and superlatives in Malay are also expressed with the use of the affixes ‘ter-’ and ‘se-’. Grammarians claim that comparatives and superlatives forms collate with adjective structure. Based on this claim, this study aims at describing the comparatives and superlatives features. The features are examined using the corpus from Korpus DBP and Corpora Collection Leipzig University. Which are then generated using Antconc. The results from Antconc show comparatives and superlatives characters and statistics. The study shows that comparatives ‘lebih’ (<> more) and ‘kurang’ (<> less) and superlatives ‘paling’ (<> most) and ‘sangat’ (<> very) forms exist with count phrase, verb phrase, and prepositional phrase. Besides, this study shows that the meanings expressed by comparatives and superlatives when combined with an adjective phrase are different from comparatives and superlatives that collocate with count phrase, verb phrase, and prepositional phrase.